Non-climacteric fruit development and ripening regulation. The Phytohormones Show. - Perotti, María Florencia; Posé-Padilla, David; Martín-Pizarro, Carmen (Oxford Academic, 2023)
Fruit ripening involves numerous physiological, structural, and metabolic changes that result in the formation of ed- ible fruits. This process is controlled at different molecular levels, with essential roles for phytohormones, transcrip- tion factors, and epigenetic modifications. Fleshy fruits are classified as either climacteric or non-climacteric species. Climacteric fruits are characterized by a burst in respiration and ethylene production at the onset of ripening, while regulation of non-climacteric fruit ripening has been commonly attributed to abscisic acid (ABA). However, there is controversy as to whether mechanisms regulating fruit ripening are shared between non-climacteric species, and to what extent other hormones contribute alongside ABA. In this review, we summarize classic and recent studies on the accumulation profile and role of ABA and other important hormones in the regulation of non-climacteric fruit develop- ment and ripening, as well as their crosstalk, paying special attention to the two main non-climacteric plant models, strawberry and grape. We highlight both the common and different roles of these regulators in these two crops, and discuss the importance of the transcriptional and environmental regulation of fruit ripening, as well as the need to optimize genetic transformation methodologies to facilitate gene functional analyses.
Keywords: Hormonas vegetales; Fitorreguladores; Fresas - Maduración; ABA; Grapevine